PENGARUH STRATEGI KOPING FANGIRLING TERHADAP TINGKAT STRES MAHASISWA FAKULTAS ILMU KESEHATAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA TAHUN 2021 - Ashri Nurfatihah Fatah (2022)
Stress is a physical or psychological reaction due to external and internal pressures. Coping strategy is an individual's way of dealing with stress, and fangirling behavior is one of the coping strategies that students do. Fangirling is the activity of female fans in consuming popular culture products such as watching videos, listening to music, watching movies/drama/reality shows, and the latest updates about artists/idols on the internet/social media. This study aims to determine the effect of fangirling coping strategies on stress levels in students of the Faculty of Health Sciences, National Veterans Development University, Jakarta in 2021. This type of research is quantitative, cross-sectional design. The sample amounted to 319 respondents, the sampling technique was purposive sampling, using gform in December 2021. Data analysis with chi-square test and research results showed that there was no relationship between fangirling coping effects and watching artist/idol videos [p-value = 0.097, OR = 1.538, 95% CI = 0.92-2.56], by listening to music of artists/idols [p-value = 0.463, OR = 1.232, 95% CI = 0.70-2.15], by watching favorite movies/drama/reality shows [p -value = 0.157, OR - 1.424, 95% CI = 0.87-2.32], and with the latest updates about artists/idols on the internet/social media [p-value e= 0.0291, OR = 1.278, 95% CI = 0.81-2.01] on student stress. It can be concluded that the fangirling coping strategy is not related to stress, so it does not affect stress on students of the Faculty of Health Sciences, Universitas Pembangunan Nasional Veteran Jakarta in 2021.